Historia en voz baja : la oralidad y el rumor para la narración de la Guerra Civil española en la 'Primera derrota' de Alberto Méndez - Sánchez, Mariela (2015)
The first of the four paths that structure the book Los girasoles ciegos, by Alberto Méndez, with its theory about the delayed end of the Spanish Civil War as a longing for destruction outside of any kind of strategy based on military logic, presents the construction of a memory based on a certain oral marks, facts provided quetly by apparently non-central characters, the distrust of written documents, and the use of speech patterns mostly associated with spontaneity in order to set up a level of verisimilitude which makes the memory emerge in parallel pathways considered relatively reliable (fort example, the case of a report), forged speech on the basis of indirect references, testimonials and letters. br /The aim of the paper is to consider an example of contemporary Spanish narrative in which a journey, perhaps weak in terms of the material, support to the channels through which the narrator comes in the story through the voice of the people, but functional as an approach to a search of the recent past, contributes to a certain conception of memory.
Keywords: Los girasoles ciegos; Memoria; Pasado traumático; Testimonios